A companion to John F. Kennedy - Selverstone, Marc J. (John Wiley & Sons Ltd, 2014)
President John F. Kennedy remains a seminal yet enigmatic figure in American politics. This collection offers an overview of Kennedy's life, presidency, and legacy, as well as a detailed look at the central arguments and scholarly debates that surround his time in office.